Emergence and clonal expansion of Vibrio aestuarianus lineages pathogenic for oysters in Europe - Aurélie Mesnil; Maude Jacquot; Céline Garcia; Delphine Tourbiez; Lydie Canier; Audrey Bidois; Lionel Dégremont; Deborah Cheslett; Michelle Geary; Alessia Vetri; Ana Roque; Dolors Furones; et al. (Molecular Ecology, 2023)
Crassostrea gigas oysters represent a significant global food source with 4.7 million tons harvested per year. In 2001, the bacterium Vibrio aestuarianus subsp. francensis emerged as a pathogen that causes adult oyster mortality in France and Ireland. Its impact on oyster aquaculture has increased in Europe since its re‐emergence in 2012. To better understand the evolutionary mechanisms leading to the emergence and persistence over time of this pathogen, we conducted a survey of mollusc diseases through national reference laboratories across Europe. We analysed 54 new genomes of Vibrio aestuarianus ( Va ) isolated from multiple environmental compartments since 2001, in areas with and without bivalve mortalities. We used a combination of comparative genomics and population genetics approaches and show that Va has a classical epidemic population structure from which the pathogenic Va francensis subspecies emerged and clonally expanded. Furthermore, we identified a specific cus‐cop ‐containing island conferring copper resistance to Va francensis whose acquisition may have favoured the emergence of pathogenic lineages adapted and specialized to oysters.

Wolbachia modulates prevalence and viral load of Culex pipiens densoviruses in natural populations - Mine Altinli; Sebastian Lequime; Celestine Atyame; Fabienne Justy; Mylene Weill; Mathieu Sicard (Molecular Ecology, 2020)
The inadequacy of standard mosquito control strategies calls for ecologically safe novel approaches, for example the use of biological agents such as the endosymbiotic α‐proteobacteria Wolbachia or insect‐specific viruses (ISVs). Understanding the ecological interactions between these “biocontrol endosymbionts” is thus a fundamental step. Wolbachia are transmitted vertically from mother to offspring and modify their hosts’ phenotypes, including reproduction (e.g., cytoplasmic incompatibility) and survival (e.g., viral interference). In nature, Culex pipiens ( sensu lato ) mosquitoes are always found infected with genetically diverse Wolbachia called w Pip that belong to five phylogenetic groups. In recent years, ISVs have also been discovered in these mosquito species, although their interactions with Wolbachia in nature are unknown. Here, we studied the interactions between a widely prevalent ISV, the Culex pipiens densovirus (CpDV, Densovirinae ), and Wolbachia in northern Tunisian C. pipiens populations. We showed an influence of different Wolbachia groups on CpDV prevalence and a general positive correlation between Wolbachia and CpDV loads. By investigating the putative relationship between CpDV diversification and w Pip groups in the different sites, we detected a signal linked to w Pip groups in CpDV phylogeny in sites where all larvae were infected by the same w Pip group. However, no such signal was detected where the w Pip groups coexisted, suggesting CpDV horizontal transfer between hosts. Overall, our results provide good evidence for an ecological influence of Wolbachia on an ISV, CpDV, in natural populations and highlight the importance of integrating Wolbachia in our understanding of ISV ecology in nature.

Population structure and adaptation of a bacterial pathogen in California grapevines - Mathieu Vanhove; Anne Sicard; Jeffery Ezennia; Nina Leviten; Rodrigo P.P. Almeida (Environmental Microbiology, 2020)
Summary Xylella fastidiosa subsp. fastidiosa causes Pierce's disease of grapevine (PD) and has been present in California for over a century. A singly introduced genotype spread across the state causing large outbreaks and damaging the grapevine industry. This study presents 122 X . fastidiosa subsp. fastidiosa genomes from symptomatic grapevines, and explores pathogen genetic diversity associated with PD in California. A total of 5218 single‐nucleotide polymorphisms (SNPs) were found in the dataset. Strong population genetic structure was found; isolates split into five genetic clusters divided into two lineages. The core/soft‐core genome constituted 41.2% of the total genome, emphasizing the high genetic variability of X . fastidiosa genomes. An ecological niche model was performed to estimate the environmental niche of the pathogen within California and to identify key climatic factors involved in dispersal. A landscape genomic approach was undertaken aiming to link local adaptation to climatic factors. A total of 18 non‐synonymous polymorphisms found to be under selective pressures were correlated with at least one environmental variable highlighting the role of temperature, precipitation and elevation on X . fastidiosa adaptation to grapevines in California. Finally, the contribution to virulence of three of the genes under positive selective pressure and of one recombinant gene was studied by reverse genetics.

Variation in Wolbachia cidB gene, but not cidA , is associated with cytoplasmic incompatibility mod phenotype diversity in Culex pipiens - Manon Bonneau; Beniamino Caputo; Aude Ligier; Rudy Caparros; Sandra Unal; Marco Perriat‐Sanguinet; Daniele Arnoldi; Mathieu Sicard; Mylène Weill (Molecular Ecology, 2019)
Endosymbiotic Wolbachia bacteria are, to date, considered the most widespread symbionts in arthropods and are the cornerstone of major biological control strategies. Such a high prevalence is based on the ability of Wolbachia to manipulate their hosts' reproduction. One manipulation called cytoplasmic incompatibility (CI) is based on the death of the embryos generated by crosses between infected males and uninfected females or between individuals infected with incompatible Wolbachia strains. CI can be seen as a modification‐rescue system (or mod ‐ resc ) in which paternal Wolbachia produce mod factors, inducing embryonic defects, unless the maternal Wolbachia produce compatible resc factors. Transgenic experiments in Drosophila melanogaster and Saccharomyces cerevisiae converged towards a model where the cidB Wolbachia gene is involved in the mod function while cidA is involved in the resc function. However, as cidA expression in Drosophila males was required to observe CI, it has been proposed that cidA could be involved in both resc and mod functions. A recent correlative study in natural Culex pipiens mosquito populations has revealed an association between specific cidA and cidB variations and changes in mod phenotype, also suggesting a role for both these genes in mod diversity. Here, by studying cidA and cidB genomic repertoires of individuals from newly sampled natural C. pipiens populations harbouring w PipIV strains from North Italy, we reinforce the link between cidB variation and mod phenotype variation fostering the involvement of cidB in the mod phenotype diversity. However, no association between any cidA variants or combination of cidA variants and mod phenotype variation was observed. Taken together our results in natural C. pipiens populations do not support the involvement of cidA in mod phenotype variation.

Sharing cells with Wolbachia : the transovarian vertical transmission of Culex pipiens densovirus - Mine Altinli; Julien Soms; Marc Ravallec; Fabienne Justy; Manon Bonneau; Mylene Weill; Anne‐Sophie Gosselin‐Grenet; Mathieu Sicard (Environmental Microbiology, 2019)
Summary Culex pipiens densovirus (CpDV), a single stranded DNA virus, has been isolated from Culex pipiens mosquitoes but differs from other mosquito densoviruses in terms of genome structure and sequence identity. Its transmission from host to host, the nature of its interactions with both its host and host's endosymbiotic bacteria Wolbachia are not known. Here, we report the presence of CpDV in the ovaries and eggs of Cx. pipiens mosquitoes in close encounters with Wolbachia . In the ovaries, CpDV amount significantly differed between mosquito lines harbouring different strains of Wolbachia and these differences were not linked to variations in Wolbachia densities. CpDV was vertically transmitted in all laboratory lines to 17%–20% of the offspring. For some females, however, the vertical transmission reached 90%. Antibiotic treatment that cured the host from Wolbachia significantly decreased both CpDV quantity and vertical transmission suggesting an impact of host microbiota, including Wolbachia, on CpDV transmission. Overall our results show that CpDV is transmitted vertically via transovarian path along with Wolbachia with which it shares the same cells. Our results are primordial to understand the dynamics of densovirus infection, their persistence and spread in populations considering their potential use in the regulation of mosquito vector populations.

Isolation, characterization and PCR multiplexing of microsatellite loci for two sub-species of terrestrial isopod Porcellio dilatatus (Crustacea, Oniscidea) - Caroline Michaud; Cassandre Chupeau; Nicolas Bech; Magali Thierry; Mathieu Sicard; Pierre Greve; Sophie Beltran-Bech (Genetica, 2016)

A host as an ecosystem: W olbachia coping with environmental constraints - Mathieu Sicard; Jessica Dittmer; Pierre Grève; Didier Bouchon; Christine Braquart‐Varnier (Environmental Microbiology, 2014)
Summary The W olbachia are intracellular endosymbionts widely distributed among invertebrates. These primarily vertically transmitted α‐proteobacteria have been intensively studied during the last decades because of their intriguing interactions with hosts, ranging from reproductive manipulations to mutualism. To optimize their vertical transmission from mother to offspring, the W olbachia have developed fine‐tuned strategies. However, the W olbachia are not restricted to the female gonads and frequently exhibit wide intra‐host distributions. This extensive colonization of somatic organs might be necessary for W olbachia to develop their diverse extended phenotypes. From an endosymbiont's perspective, the within‐host environment potentially presents different environmental constraints. Hence, the W olbachia have to face different intracellular habitats, their host's immune system as well as other microorganisms co‐occurring in the same host individual and sometimes even in the same cell. A means for the W olbachia to protect themselves from these environmental constraints may be to live ‘hidden’ in vacuoles within host cells. In this review, we summarize the current knowledge regarding the extent of the W olbachia pandemic and discuss the various environmental constraints these bacteria may have to face within their ‘host ecosystem’. Finally, we identify new avenues for future research to better understand the complexity of W olbachia 's interactions with their intracellular environment.

Horizontal transfers of feminizing versus non‐feminizing W olbachia strains: from harmless passengers to pathogens - Winka Le Clec'h; Maryline Raimond; Sylvain Guillot; Didier Bouchon; Mathieu Sicard (Environmental Microbiology, 2013)
Summary The endosymbiont W olbachia pipientis infects various hosts in which it navigates vertically from mothers to offspring. However, horizontal transfers of W olbachia can occur between hosts. The virulence of the horizontally acquired W olbachia can change in the new host as it has been illustrated by the case of the feminizing strain w V ul C from the woodlouse A rmadillidium vulgare that turns to a pathogen when introduced into P orcellio dilatatus dilatatus. In the present study, we aim to show whether symbiotic traits, such as (i) host sex manipulation and (ii) colonization patterns, which differ between eight isopod W olbachia strains, are connected to their virulence towards the recipient host P . d. dilatatus . Among the transferred W olbachia , some feminizing strains gradually differing in feminizing intensity in their native hosts induced different levels of pathogenicity to P . d. dilatatus . Not a single feminizing strain passed vertically with high titres to the next generation. The non‐feminizing W olbachia strains, even if they reached high densities in the host, did not impact host life‐history traits and some vertically passed with high titres to the offspring. These results suggest that a potential link between the manners W olbachia manipulates its native host reproduction, its virulence and its ability to vertically infect the offspring.

Variations of immune parameters in terrestrial isopods: a matter of gender, aging and Wolbachia - Mathieu Sicard; Frédéric Chevalier; Mickaël De Vlechouver; Didier Bouchon; Pierre Grève; Christine Braquart-Varnier (The Science of Nature, 2010)

Steinernema boemarei n. sp. (Nematoda: Steinernematidae), a new entomopathogenic nematode from southern France - Ming-Min Lee; Mathieu Sicard; Marjorie Skeie; S. Patricia Stock (Systematic Parasitology, 2009)

The effect of Photorhabdus luminescens (Enterobacteriaceae) on the survival, development, reproduction and behaviour of Caenorhabditis elegans (Nematoda: Rhabditidae) - Mathieu Sicard; Sebastian Hering; Rebecca Schulte; Sophie Gaudriault; Hinrich Schulenburg (Environmental Microbiology, 2007)
Summary The free‐living soil nematode Caenorhabditis elegans interacts with diverse microorganisms in its natural habitat. These microorganisms may serve as a food source or represent a harmful threat. As such, they constitute one of the most important ecological factors of the worm’s natural environment. In this study, we examined the interaction between two natural isolates of C. elegans and three natural isolates of the entomopathogenic bacterium Photorhabdus luminescens. Two of the tested P. luminescens strains were clearly pathogenic. They consistently reduced the worm’s developmental, survival and reproductive rate, most likely through the production of nematicidal compounds. The third natural isolate tested did not decrease worm fitness. These differences could be associated with a deletion of one gene ( tcdA4 ) (∼7kb) of the toxin complex D pathogenicity island, which was found in only the non‐pathogenic strain. Our study additionally highlights the importance of behaviour in defence. Caenorhabditis elegans showed two distinct avoidance behaviours towards the pathogenic but not the non‐pathogenic P. luminescens strains. In particular, nematodes physically escaped and also reduced the ingestion of pathogenic bacteria. Our results strongly suggest that C. elegans possesses the capacity to distinguish between and subsequently respond to harmful and non‐harmful strains of the same bacterial species. The underlying mechanisms of such interactions are currently unknown. Their dissection will represent a major challenge for future research and should enhance our knowledge of the ecology of this important model organism in biological research.

Specialization of the entomopathogenic nematode Steinernema scapterisci with its mutualistic Xenorhabdus symbiont - Mathieu Sicard; Hervé Ramone; Nathalie Le Brun; Sylvie Pagès; Catherine Moulia (The Science of Nature, 2005)